MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI KECAMATAN BELAWANG (MULTI KASUS SDN BELAWANG 1 DAN SDN PARIMATA 1) - Renny Fitriati,; Khuzaini, Khuzaini; Muhammad Yuliansyah, (Journal of Innovation Research and Knowledge, 2023)
Research objectives To find out the principal's leadership planning in improving teacher performance at SDN Belawang 1 and SDN Parimata 1, 2) To find out the implementation of the principal's leadership in improving teacher performance at SDN Belawang 1 and SDN Parimata 1, 3) To find out the evaluation of the principal's leadership in improve teacher performance at SDN 1 Belawang and SDN 1 Parimata Belawang 1 and SDN Parimata 1. This study uses a qualitative research method with a phenomenological approach. The use of this method is based on the reason that the focus in this study is the leadership of the principal in improving teacher performance. Meanwhile, the phenomenological approach aims to describe the meaning of the life experiences experienced by several individuals, regarding concepts or phenomena. The results of the study 1) the planning that was made before the implementation of a program in the fields of curriculum, student affairs, and infrastructure, from changing the K13 curriculum to the Mardeka curriculum, for the students of the two schools had different ways of using literacy, gymnastics, reading the Koran, scouting, and for infrastructure facilities are less supportive for one school while school one for infrastructure facilities is adequate. 2) implementation of teacher performance The implementation of facilities is still lacking, it cannot be said that it is ready to implement delays in budgeting BOS funds, the current lesson plan uses teaching modules because it is made beforehand before implementation. and less time of execution. 3) evaluation before carrying out the assessment the teacher gets an implementation schedule in the form of lesson plans to assessments in class when learning an assessment is carried out by the principal of the suitability of the teaching module plans made and the implementation carried out, methods that can make children focus on media that support learning.